2007
DOI: 10.1097/01.tp.0000266579.11595.95
|View full text |Cite
|
Sign up to set email alerts
|

Dual Kidney Transplantation: A Case-Control Comparison With Single Kidney Transplantation From Standard and Expanded Criteria Donors

Abstract: DKT using kidneys from marginal ECDs is a viable option to counteract the growing shortage of available organs. Excellent short-term results and renal function can be achieved with older, low nephron mass donors provided that both kidneys are transplanted into a single recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 12 publications
1
49
1
1
Order By: Relevance
“…Previous studies have reported comparable allograft survival between carefully selected DKT and single kidney transplants (2)(3)(4)(5)(6)(7)(11)(12)(13)(14). Moore et al (15) recently reported results from a single center case control study comparing outcomes of 16 DKT, with ECD and SCD transplants and reported similar 2-year patient and allograft survival between DKT, SCD, and ECD transplants. However, they noted higher rates of DGF and complication rates in the SCD group than reported norms.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have reported comparable allograft survival between carefully selected DKT and single kidney transplants (2)(3)(4)(5)(6)(7)(11)(12)(13)(14). Moore et al (15) recently reported results from a single center case control study comparing outcomes of 16 DKT, with ECD and SCD transplants and reported similar 2-year patient and allograft survival between DKT, SCD, and ECD transplants. However, they noted higher rates of DGF and complication rates in the SCD group than reported norms.…”
Section: Discussionmentioning
confidence: 80%
“…Two of the 10 donors whose kidneys were used in a DKT in Lee's study did not fit an ECD definition . Andres, Remuzzi, Johnson, D'Arcy, Veroux M, Gaber, Moore, and Veroux P all used a biopsy score to determine dual allocation . Ekser used a biopsy score if the patient had elevated creatinine, hypertension, or diabetes as well as being over 60.…”
Section: Resultsmentioning
confidence: 99%
“…DKT has been shown to be effective when appropriate donors and recipients are chosen. Although DKT may involve greater anesthetic and surgical risk, it is associated with significantly higher rates of immediate graft function, especially when kidneys are acquired from extended criteria donors …”
Section: Introductionmentioning
confidence: 99%
“…In patients awaiting kidney transplantation alone, some studies have evaluated an approach that involves transplanting both kidneys from a single donor when an individual kidney from such a donor may be deemed unsuitable and discarded. Transplanting both kidneys together is thought to offset the decrease in quality, with some studies demonstrating comparable recipient outcomes to those seen with single‐kidney transplantation using extended criteria donor (ECD) organs …”
mentioning
confidence: 99%